Coming Together to Toast and Feed the Dead in the Cotahuasi Valley of Peru - Mayer, Aaron Jay; Sayre, Matthew; Jennings, Justin (Ethnobiology Letters, 2017)
There has been little discussion on the macrobotanical remains from Andean Middle Horizon sites. In this article, we present macrobotanical data from archaeological excavations at Tenahaha, a small mortuary center in the Cotahuasi Valley of Peru. While the people who attended Tenahaha may not have definitively been Wari, evidence suggests that they were likely influenced by the Wari. Our analysis revealed new insights into site use and the distribution of botanical staples during the Andean past. People used plants differently across time and how people chose to utilize plant resources from their environment provides insights into cultural practices. The local plant staples of quinoa (Chenopodium quinoa) and maize (Zea mays) were found in high densities in concentrated areas of the site. In addition, local plants such as Echinocactus (Echinocactus sp.), tubers (e.g., Solanum sp.), and the Peruvian peppertree (Schinus molle) were recovered in abundance. These remains provide insights into past public ceremonies and how the inhabitants used different areas of the site. The occurrence of sprouted maize and the fruit of peppertree in certain areas of the site seems to indicate ritual and/or ceremonial use of chicha during the Middle Horizon (AD 600–1050). The analysis of these macrobotanical remains provides a glimpse into the importance placed on bringing people together to commemorate the dead by Ancient Andean Peoples.